2016
DOI: 10.5588/ijtld.14.0930
|View full text |Cite
|
Sign up to set email alerts
|

Association of human leukocyte antigen DRB1 polymorphism and tuberculosis: a meta-analysis

Abstract: These results reinforce the importance of HLA-DRB1 alleles in the development of infectious diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…All 15-mer mTCEs tested showed high affinity predicted binding to multiple DR alleles (>60%) prevalent in India (Figure 6C: refer to median percentage of each group of mTCEs binding to Group A DR alleles), with the exception of mTCEs equal in India and outside India and mTCEs enriched outside India, which showed predicted binding to only few (<35% median) DR alleles. Interestingly, HLA-DRB1 * 03, HLA-DRB1 * 04 & HLA-DRB1 * 08 have been associated with TB protection/disease (68, 69); Group-A includes HLA-DRB1 * 03:01, * 04:02, * 04:08, and * 04:10 all of which bind ≧60% (>12/20) peptides tested with high predicted binding affinity. Together, these data provide strong evidence that MHC Class II DR binding patterns likely reflect whether an mTCE is (i) exclusive to India, (ii) enriched in India but can be found infrequently globally, (iii) in equal proportion in India vs. the rest of the world or (iv) enriched outside India.…”
Section: Resultsmentioning
confidence: 99%
“…All 15-mer mTCEs tested showed high affinity predicted binding to multiple DR alleles (>60%) prevalent in India (Figure 6C: refer to median percentage of each group of mTCEs binding to Group A DR alleles), with the exception of mTCEs equal in India and outside India and mTCEs enriched outside India, which showed predicted binding to only few (<35% median) DR alleles. Interestingly, HLA-DRB1 * 03, HLA-DRB1 * 04 & HLA-DRB1 * 08 have been associated with TB protection/disease (68, 69); Group-A includes HLA-DRB1 * 03:01, * 04:02, * 04:08, and * 04:10 all of which bind ≧60% (>12/20) peptides tested with high predicted binding affinity. Together, these data provide strong evidence that MHC Class II DR binding patterns likely reflect whether an mTCE is (i) exclusive to India, (ii) enriched in India but can be found infrequently globally, (iii) in equal proportion in India vs. the rest of the world or (iv) enriched outside India.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, in a population from South Africa, DRB1*08: 03 allele has found to be strongly positively associated with drug-resistance, increase in lung damage and resurgence of TB [75] . Another recent meta-analysis including 19 case-control studies also confirmed the DRB1*03 protection and DRB1*08 risk effect and added DRB1*04 and DRB1*16 as markers associated with an increased infection occurrence, concluding also that both ethnicity and genotyping methods affect the association between several HLA-DRB1 alleles and TB occurrence [76] . Confirming DRB1*04, DRB1*15 and DRB1*16, and adding DRB1*09 and DRB1*10 as polymorphisms that may contribute to the risk of TB, especially in East Asian, and identifying DRB1*11 as conferring protection, a 31 studies meta-analysis fail to support a significant association between the HLA-DRB1*01, *03, *07, *08, *12, *13, and *14 gene polymorphisms and TB risk [77] .…”
Section: Pulmonary Tuberculosismentioning
confidence: 92%
“…Finally, the few existing HLA association studies in individuals of African ancestry indicate considerable deviation from the effects in other groups, the majority of which were identified in individuals of European or Asian populations (Fingerlin et al, 2015;Malkova et al, 2020;Tong et al, 2015;Yang et al, 2016). This study probed for HLA associations with outcomes of Mtb exposure in individuals from a densely populated region of Kampala, Uganda (Mchenry et al, 2021;Stein et al, 2018Stein et al, , 2019, whereas associations with sarcoidosis outcomes were assessed in Americans of African ancestry (ACCESS Research Group, 1999;Baughman et al, 2001;Rybicki et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Variants within the human leukocyte antigen (HLA) genomic region are associated with both active tuberculosis disease (Tong et al, 2015; Yang et al, 2016) and sarcoidosis (Fingerlin et al, 2015). The class II HLA loci: DRB1, DQB1, and DPB1 are of particular concern due to their central role in antigen recognition and presentation to helper T cells via antigen‐presenting cells, which is the initial mechanism leading to granuloma formation and persistence that characterizes both tuberculosis disease and sarcoidosis (Grunewald et al, 2019).…”
Section: Introductionmentioning
confidence: 99%